BIOGRAPHISTIC RESOURCES OF LITHUANIAN BOOK WORKERS 1918–1944 - JAKIMAVIČIŪTĖ, IVETA (Knygotyra, 2015)
In the article there is provided analysis of main and valuable in abundance of information biographic resources of book workers published in period of 1918–1944. On the basis of results of the analysis there are provided reasoned conclusions about the resources and information about Lithuanian book workers. Lithuanian national culture was created by many outstanding personalities during discussed period. Creators of the main biographistic publications that drew frames for further development of the item were prof. Vaclovas Biržiška, Ansas Bruožis, Antanas Milukas, Petras Ruseckas, Juozas Tumas-Vaižgantas. In the article there were analysed main publications that became the significant biographistic resources of book personalities and till now they are valuable. These personalities could be named as representatives of the first Lithuanian book science biographistic school, because they defined trends for researches and methodology for further scientific investigations. During Lithuanian independency (1918–1944) as a significant resource of biographistic informatikon could be named periodicals such as “Bibliografijos žinios”, “Mūsų Senovė”, “XXVII knygos mėgėjų metraštis”, “Kultūra”, “Literatūros naujienos”, etc. On the basis of the analysis of biographistic resources of book workers there were made conclusion that in investigated period (1918–1944) biographistic resources of book personalities are not numerous. Preparation and publication of those resources were important and relevant for culture and art of these days. Certainly J. Tumas-Vaižgantas, P. Ruseckas V. Biržiška and others were among those who made efforts to make these publications. Typical activities for that period were lectures about personalities, later they were changed by publications in periodicals. Afterwards publications were complemented, there were made some corrections and texts were published in particular books or few sheets’ booklets. Because of the shortage of time publications had some mistakes, inaccuracy and some fictitious facts, biographistic data was fragmented; only some episodes or their fragments were provided. (This kind of imprecision was typical for Vaižgantas and he was criticized by others for that). Though publications and articles in periodicals were written not in scientific way, not highly theoretical and circumstantial, without providence and evaluation of publishers, yet they provide valuable data about book workers for investigation.